Optimization of the textile wastewater pretreatment process in terms of organics removal and microplastic detection. (15th January 2023) - Akyildiz, Sinem Hazal; Sezgin, Hande; Yalcin, Bahattin; Yalcin-Enis, Ipek
Abstract: The textile industry, which offers innovative and diversified products to meet the rising demand, comes to the fore with the damage it causes to the environment. In the modern world, where synthetic fibers made from petroleum derivatives dominate the textile sector, it is evident that plastic wastes at macro, micro, and nano scales put the health of all living things at risk. The release of microplastics into the environment is significantly affected, especially from wastewater treatment plants. The primary goal of this study is to identify the most effective pretreatment approach for reducing organic matters in textile wastewater to in order to better detect microplastics and microfibers. For this, synthetic microfibers containing acrylic, polyester, and polyamide were put through various procedures using H2 O2, Fenton's reagent, HCl, KOH, and NaOH under two different process conditions (25 °C for 5 days and 60 °C for 6 h). The outcomes revealed that H2 O2 was the most efficient chemical for separating organic from textile wastewater, while KOH and NaOH resulted in physical and chemical damages for all polymer types. Although it was noted that HCl and Fenton's reagent did not affect other microfibers, they had been found to alter the physical structure of polyamide, making it more challenging to extract from wastewater. In addition, the use of heat had no further effect on the separation and merely served to speed up the procedure.